New Perspectives on Nationalism in Spain - Humlebæk, Carsten Jacob; Ruiz Jiménez, Antonia María (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The Spanish nation has been contested almost since its conception in the early nineteenth century, and the Spanish state has therefore been involved in perpetual conflicts between various nationalisms, particularly between different versions of Spanish nationalism as well as between Spanish majority nationalism and various minority nationalisms. At different times in history, the conflicts have revived and turned into organizing principles of the political communities in Spain, as communities in conflict or contention but, nevertheless, as communities providing the Spaniards with different senses of belonging. In recent times, both lines of contention have been activated again, and in this volume, we focus particularly on the conflict between majority and minority nationalism, which has been revived from approximately 2010 around the Catalan separatist conflict, but other sub-state identities are potentially conflictual as well. Both the state-wide - Spanish - as well as the sub-state actors try to develop feelings of territorial attachments to the Spanish political community or to the respective sub-state political communities, and both use emotions and feelings to secure support and to assert or claim sovereignty for the political community in question. The contributions in this volume shed light on various issues related to these questions.